Dampak pemberian instruksi pembersihan gigi tiruan lengkap dengan menggunakan leaflet terhadap kualitas hidup lansia (kajian di panti wreda kasih bapa, pontianak tenggara) - Niko Falatehan; Juan Justin John (Jurnal Kedokteran Gigi Terpadu, 2023)
Patient instruction is a crucial factor that could affect the outcome of complete denture treatment. Leaflet is one of the written media that is frequently utilized to provide information and instruction. Effective instruction will help patients maintain good behavior towards cleaning their dentures thus affecting their quality of life. This study aims to determine the impact of written instructions with the use of leaflet regarding complete denture cleaning on the oral health related quality of life in elderly patients. 36 elderly patients are interviewed and instructed with leaflet. The quality of life is assessed with OHIP-EDENT questionnaire. Data is collected twice, before the patients were given the instructions 1 month after the patients were given the instructions. Before receiving written instructions, most of the patients have a moderate quality of life (86,11%). After receiving instructions most of the patients have good quality of life (55,56%). Statistical test showed significant impact of leaflet instruction regarding complete denture cleaning on the oral health related quality of life of elderly patients. There is a significant impact of written complete denture cleaning instructions on the oral health related quality of life on elderly patients.